Therapeutic Plasmapheresis: Indications and Clinical Outcomes - Ignarska, Justyna; Ignarska, Magdalena; Kubicz Mzabi, Sabina; Kaus, Marta; Podhorecka, Monika (Journal of Education, Health and Sport, 2026)
Therapeutic plasma exchange is a procedure that involves separating plasma from the cellular components. The plasma that is taken out is discarded and swapped with a solution that includes both crystalloid and colloid components or fresh frozen plasma also.[1] Therapeutic plasmapheresis (TP) is used to treat autoimmune diseases, certain poisonings, and any other conditions where there is a need to rapidly eliminate toxins from the bloodstream. The most important part of plasmapheresis is separation plasma and exchange with plasma of donors. The change of action of the immune system is secondary. During the process, large amounts of plasma can be replaced without putting too much strain on the circulation.[2] This review provides us with information about plasmapheresis, comprehensive examination of its methods, indications, and effects within hematological disorders. It explores potential future directions for the development of plasmapheresis, shedding light on emerging trends and innovations in the field. The article provides a brief analysis of the advantages and disadvantages associated with the use of plasmapheresis. It also compares plasmapheresis to commonly employed treatment methods for a specific disease entity.